2005
DOI: 10.1177/154405910508401117
|View full text |Cite
|
Sign up to set email alerts
|

Chewing Indicators between Adults with Down Syndrome and Controls

Abstract: Down syndrome induces a neuromotor deficiency that affects the orofacial musculature, and thus could be implicated in the feeding difficulties affecting people with this disease. This study aimed to investigate the differences in chewing indicators between a group of 11 adults with Down syndrome and a group of 12 healthy subjects without Down syndrome. Chewing ability was evaluated by means of video recordings taken during a standardized meal that included 10 natural foods. The variables collected were mastica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 30 publications
2
28
1
Order By: Relevance
“…This is a paradoxical result, as previous studies reported that for a given standardized food, subjects with poor oral conditions such as denture wearers Veyrune et al, 2007] or patients with Down syndrome [Hennequin et al, 2005], have lower chewing frequencies than subjects with good oral health. It could be hypothesized that the subjects with caries who have few PFUs have adopted a new chewing strategy, using their anterior teeth to cut or crush the food.…”
Section: Effects Of Carious Process On Chewing Activity Adaptation Tocontrasting
confidence: 45%
See 1 more Smart Citation
“…This is a paradoxical result, as previous studies reported that for a given standardized food, subjects with poor oral conditions such as denture wearers Veyrune et al, 2007] or patients with Down syndrome [Hennequin et al, 2005], have lower chewing frequencies than subjects with good oral health. It could be hypothesized that the subjects with caries who have few PFUs have adopted a new chewing strategy, using their anterior teeth to cut or crush the food.…”
Section: Effects Of Carious Process On Chewing Activity Adaptation Tocontrasting
confidence: 45%
“…Video recording was used for evaluation of kinematic parameters [Hennequin et al, 2005;Nicolas et al, 2007]. A digital camera positioned in front of the subject recorded facial movements.…”
Section: Methodsmentioning
confidence: 99%
“…This is probably not the case, however, because the reliability was assessed between two successive recording sessions. The visual observation method has been used successfully in other studies [4,5,15,[29][30][31] and the methodology for evaluating mastication has been validated in disabled patients [32,33].…”
Section: Particle Size Distribution Depends On Food Type and Not On Imentioning
confidence: 99%
“…The slot Textural parameters represents the perception of the mechanical behaviour of the food such as elasticity, plasticity, hardness, thickness viscosity, toughness, chewiness, adhesiveness, cohesiveness, springiness, resilience, firmness, gumminess, stickness, rubberiness, brittleness (fracturability), crispness, crunchiness, crackliness, tenderness, juiciness, mealiness, etc. (Bourne, 2002;Foster et al, 2006;Hennequin et al, 2005;Lucas, 2004;Mioche et al, 1999;Peyron et al, 2002;Woda et al,2006aWoda et al, , 2006bYomoda et al, 2004). As these textural parameters are ambiguous and even synonymic, an appropriate definition of theirs will be required.…”
Section: Food Propertiesmentioning
confidence: 96%
“…A chewing cycle mostly refers to an event of jaw opening and closing in the vertical plane that is repetitive in the sequence of the mastication. The masticatory frequency can be therefore calculated by the number of cycles of the sequence divided by sequence duration (Hennequin, Allison, Faulks, Orliaguet, & Feine, 2005;Lassauzay et al, 2000). For a given food, the chewing cycle is highly characteristic for each individual people (Woda, Mishellany, & Peyron, 2006b), so that it has been measured by various features, such as cycle shape in three dimensions and cycle duration (Buschang, Hayasaki, & Throckmorton, 2000).…”
Section: Masticatory Eventsmentioning
confidence: 99%